Pengaruh Desain Produk, Harga Dan Labelisasi Halal Terhadap Keputusan Pembelian Mie Samyang Masyarakat Bidar Alam Solok Selatan - Pram Agusta; Maria Magdalena (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to examine the effect of product design on purchasing decisions for samyang noodles in the Bidar Alam Solok Selatan community. to test the effect of price on purchasing decisions for samyang noodles, the people of Bidar Alam Solok Selatan. And to test the effect of halal labeling on purchasing decisions for samyang noodles, the people of Bidar Alam Solok Selatan. This type of research is quantitative, where this research uses numerical data and the research process emphasizes objective measurement of results using statistical analysis. The population in this study are people who buy samyang noodles. The sampling technique used is purposive sampling. The number of samples is 70 people obtained by using the hair formula. The types of data used in this study are quantitative and qualitative data. The data sources are primary and secondary data sources. The data analysis technique uses multiple linear regression with the help of the SPSS version 21.00 program. The hypothesis was tested using the t test at α = 0.05. The results of this study indicate that product design, price and halal labeling have a positive and significant effect on purchasing decisions for samyang noodles for the people of Bidar Alam Solok Selatan.